Student’s Perception of Using Powtoon As A Learning Media in Teaching Speaking at SMPN 14 Bengkulu Tengah: English - Puspitasari; Sujarwati, Iis (ETERNAL (English Teaching Journal), 2024)
This study aimed to discover students' perceptions of using animation videos from Powtoon as learning media on the greeting card topic, especially for their speaking ability. This study was carried out at SMPN 14, Bengkulu Tengah, in the eighth grade. The present study employed a quantitative research methodology in survey research design. Twelve VIII-A students who were selected through the use of the purposive sampling technique served as the research samples. A Likert scale was used to assess the data that were gathered from a questionnaire regarding students' perceptions. The mean score of each questionnaire item was then categorized using interval score interpretation. The study's conclusions showed that students' perceptions of Powtoon's use as a teaching tool in speaking classes were positive. All 11 questionnaire items (73,3%) obtained the “very good” category, and 4 questionnaire items (26,7%) obtained the “good category.” In conclusion, the majority of the students agreed that Powtoon makes the learning process more interesting and makes absorbing the material easier, increasing students pronunciation and vocabulary mastery. The teacher also benefited in terms of producing interesting and fun speaking lesson videos